The coronary dilation effect of shen fu injection was mediated through NO. - Yu Hong Li; Bin Yu; Zhen Zhen Duan; Olunga Mary Akinyi; Jia Hui Yu; Kun Zhou; Yue Zhang; Xiu Mei Gao (PLoS ONE, 2014)
OBJECTIVES: Shen Fu Injection (SF), which consisted of Red ginseng extraction injection (RG) and prepared aconite extraction injection (RA), is a traditional Chinese medicine mainly used for various cardiac diseases. This study is to analyse SF's effects on cardiac performance and coronary circulation. And the coronary dilating effect and mechanism of the above three injections were also explored. METHODS: Mature male guinea pigs were used as our animal model. We employed two types of perfusion methods (constant pressure and constant flow) in vitro, using Langendorff heart preparations to observe the cardiac function and coronary response to SF (1/200). The coronary dilation effects of the above three injections (1/800, 1/400 and 1/200) were recorded at basal coronary resting tone and when coronary vessels were pre-contracted with a thromboxane A2 analogue (U46619), in the presence or the absence of the inhibitor of nitric oxide synthesis (L-NAME, 10-4 M), the blocker of Ca2+-activated potassium channel(TEA, 10-3 M), or the blocker of adenosine triphosphate (ATP)-sensitive potassium channel (glybenclamide) (10-5 M). RESULTS: When perfused with constant pressure, SF significantly increased coronary flow, left ventricular developed pressure (LVDP) and the rate-pressure product (RPP). When perfused with constant flow, SF produced a significant reduction in the coronary perfusion pressure (CPP), LVDP and RPP. The coronary vasodilatation response of the above three injections can be reduced by L-NAME but was unaffected by TEA or glybenclamide when coronary vessels were pre-contracted with U46619 but not at resting tone. SF, RG and RA can all up-regulate eNOS expression in the human umbilical vein cells (EA.hy926). CONCLUSION: We demonstrated that SF does not contribute to the inotropic change of myocardium whose improvement is due to alternation of coronary flow. The coronary dilation effect of SF was mediated through RG and RA, via promoting NO release.